Hubungan Beban Kerja Perawat Dengan Peran Perawat Anak Dalam Pendampingan Terapi Bermain - Ririn Nur Indah sari; Sari Windyastuti; Tri Sakti Widyaningsih (Poltekkes Kemenkes Jakarta III, 2019)
Nurse workload is very influential on child play therapy assistance caused by workload excessive workload, lack of facilities and infrastructure, nothing schedule for play therapy and the number of nurses only 18 nurses, According to theory Gilles with the number of beds 34 needed 29 nurses. The purpose of this research is to know the Relationship of Nurse Workload with The Role of Child’s Nurse in Mentoring Play Therapy in Room Dahlia RSUD Dr. H Sewondo Kendal. This type of research is descriptive correlation with cross sectional. The sampling technique with total sampling, a sample is 18 respondents. Retrieval data using questionnaires and then tested into Spearman Rank test statistic. Based on research found 10 respondents (55,6%) have hard workload and 8 respondents (44,4%) have a light workload. The role of nurses in good categories 5 respondents (27,8%) and categories less is 13 respondents (72,2%). From result of Spearman Rank test analysis, get result of coefficient correlation value -868 in category very strong and obtained p value = 0,000 < 0,05 it’s mean Ha accepted and H0 rejected. There is a relantionship between the nurses workload with the role of child nurses in mentoring play therapy.